2017
DOI: 10.1186/s12882-017-0667-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of early versus late initiation of renal replacement therapy for acute kidney injury in critically ill patients: an updated systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundTo investigate the impact of timing the initiation of renal replacement therapy (RRT) on clinical outcomes in critically ill patients with acute kidney injury (AKI), focusing on the randomized controlled trials (RCTs) in this field.MethodsThe PubMed, EMBASE and Cochrane databases were searched between January 1, 1985, and June 30, 2016, to identify randomized trials that assessed the timing of initiation of RRT in patients with AKI.ResultsNine RCTs, with a total of 1636 patients, were enrolled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 24 publications
4
36
1
Order By: Relevance
“…Data about optimal timing of RRT is a controversy. In an adult setting there are some reports showing the survival benefits of early RRT while recent meta‐analyses show no effect of early RRT . Two large multi‐centre randomized trials show conflicting results as well .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data about optimal timing of RRT is a controversy. In an adult setting there are some reports showing the survival benefits of early RRT while recent meta‐analyses show no effect of early RRT . Two large multi‐centre randomized trials show conflicting results as well .…”
Section: Discussionmentioning
confidence: 99%
“…In an adult setting there are some reports showing the survival benefits of early RRT 23 while recent meta-analyses show no effect of early RRT. [24][25][26] Two large multi-centre randomized trials show conflicting results as well. 27,28 The data about the timing of RRT in paediatric AKI is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier retrospective and prospective studies revealed the survival benefits of early RRT initiation; however, since the AKIKI and ELAIN trials published in 2016, these survival benefits have become debatable. In recent years, several meta-analyses have been published, most of which investigated prospective or retrospective studies owing to the lack of large-scale randomized controlled trials (RCTs), and in these meta-analyses, a definitive conclusion regarding the optimal time of RRT initiation could not be drawn [5][6][7][8][9][10][11]. Conventional indications (refractory fluid overload, acidemia, hyperkalemia, and uremic complication) for RRT initiation are indisputable over several years.…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous studies investigating the relationship between mortality and the timing of RRT initiation, it remained controversial whether early initiation of RRT improved outcomes. In 2016, two RCTs and in 2017 nine systematic reviews and meta‐analyses evaluated the optimal timing of RRT initiation for AKI. A multicenter RCT study, the Artificial Kidney Initiation in Kidney Injury (AKIKI) study, conducted in France, showed that there were no significant differences in mortality between early and late initiation of RRT .…”
Section: Rrt For Akimentioning
confidence: 99%
“…Early initiation of RRT (defined as KDIGO stage 3 AKI) in the AKIKI study corresponded to the delayed arm in the ELAIN study. Turning to the conclusions of nine meta-analyses,[90][91][92][93][94][95][96][97][98] the AKI patients in the RCTs who underwent early initiation of RRT did not show a lower mortality rate than those with late RRT [90][91][92][93][94]96,98.…”
mentioning
confidence: 99%